Epic adventures and emotional journeys: How participation in comic conventions and live action role plays is associated with psychosocial outcomes - Hajek A.; Zwar L.; Gyasi R. M.; Oh H.; Yon D. K.; Veronese N.; SOYSAL P.; König H.; Pengpid S.; Peltzer K. (My University, 2025)
Aim: Our aim was to examine the association of visiting comic conventions (including cosplay) and attending live-action role-playing games (LARPs) with psychosocial outcomes (in terms of mental health, subjective well-being, and social disconnectedness). Subject and methods: Data were taken from a quota-based sample (representing the general German adult population aged 18 to 74 years, n = 5000). The average age was approximately 47 years. Participation in comic conventions (including cosplay) and LARP events were key independent variables. Psychometrically sound tools were used to quantify the psychosocial outcomes. Adjusted linear regression models were applied. Results: Individuals visiting comic conventions had significantly poorer mental health (depressive and anxiety symptoms, social withdrawal) than non-participants. They also had higher loneliness and perceived social isolation levels, but lower objective social isolation levels. They did not differ from non-participants in terms of well-being outcomes. Individuals attending LARPs also had more depressive and anxiety symptoms but did not differ in terms of social withdrawal. They had higher perceived social isolation levels but had lower objective social isolation levels. Furthermore, they had more favorable well-being outcomes than non-participants. Cosplay during comic conventions and current attendance of LARPs were associated with both positive and negative outcomes. Conclusion: Visitors to comic conventions and LARPs sometimes had poorer psychosocial outcomes relative to non-visitors, especially in the area of mental health. However, LARP participants had better well-being outcomes than non-participants. This knowledge can help identify specific groups at risk of poor psychosocial outcomes.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; Sosyal Bilimler (Soc); Sosyal Bilimler Genel; Kamu Çevre ve İş Sağlığı; Social Sciences (Soc); Social Sciences General; Public Environmental & Occupational Health; Halk, Çevre ve İş Sağlığı; Sağlık Bilimleri; Public Health, Environmental and Occupational Health; Health Sciences; Anxiety; Comic con; Cosplay; Depression; Fandom; Hikikomori; Ikigai; LARP; Life satisfaction; Live action role playing; Loneliness; Mental health; Nerd; Purpose in life; Social isolation; Social withdrawal